A Maximally Flat Design of RC-Active Low-Pass Filters with Sharp Cutoff by Cascading Third-Order Blocks - Thajchayapong, P.; Punkasirikul, C. (My University, 1986)
A design technique for a multiple real root maximally flat (MURROMAF) with coincident pairs of transmission zeros is described. In comparison with previous reports, the technique offers two main advantages. First, the passband magnitude responses show no distortion with respect to the maximally flat criterion. Secondly, there is more freedom on the choices of the real pole multiplicity and the number of coincident pairs of the transmission zeros as long as the realizability condition is observed. © 1986 IEEE